The good internationalist: U.S. responses to trade-offs in internationalized security policy in the 1995 Bosnia debate - Katharina Emschermann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2013)
When representatives of the U.S. government and Congress debated military intervention in the conflict in Bosnia in 1995, they were not just talking about an American troop contribution. The dispute became a focal point for issues such as relations with the U.N. and NATO and the general desirability of multilateral peacekeeping. What elicited the strong responses were trade-offs inherent to the internationalization of security policy: security gains were measured against concerns about the national interest, democratic legitimacy, and effects on the rule of law. However, despite their role in shaping future policy these types of responses lack systematic analysis. Following a qualitative content analysis, this paper offers a response overview. I distinguish three phases in the debate and illustrate that turning points were brought on by the momentum of events in the Balkans rather than D.C. Yet, arguments seem to have developed a 'symbolic power' independent of their direct effect on the course of events. While the U.N. was strongly contested NATO proved to be a 'common denominator' with some disciplining power over internationalization's critics. In defense of the intervention, the Clinton administration portrayed multilateralism as a useful tool. This strategy helped sell internationalization to Congress. But it also required a non-committal rhetoric which would serve opponents of international security organizations beyond 1995. – – Als Vertreter der U.S. Regierung und des Kongresses 1995 über eine militärische Intervention in Bosnien diskutierten, stand nicht nur ein amerikanischer Truppenbeitrag zur Debatte. Das Thema war Anlass für eine grundsätzliche Auseinandersetzung über das Verhältnis zur UNO, zur NATO und darüber, inwieweit friedensschaffende Maßnahmen im Verbund wünschenswert seien. Die Heftigkeit der Reaktionen lässt sich auf Güterkonflikte zurückführen, die mit der Internationalisierung von Sicherheit einhergehen: Zugewinne an Sicherheit durch internationale Organisationen werden abgewogen gegen das nationale Interesse, demokratische Legitimität und Rechtsstaatlichkeit. Obwohl diese Reaktionen Einfluss auf zukünftige Politik nehmen können, sind sie bisher nicht systematisch erforscht worden. Basierend auf einer qualitativen Inhaltsanalyse, liefert dieses Papier einen Überblick über die Reaktionstypen der Bosnien-Debatte. Ich unterteile die Debatte in drei Phasen und zeige, dass die Eigendynamik der Entwicklungen im Balkan die Richtung stärker beeinflusste als Washington. Dennoch entfalteten die vorgebrachten Argumente unabhängig von ihrem direkten Einfluss eine 'symbolische Kraft'. Während die UNO stark umstritten war, erwies sich die NATO als kleinster gemeinsamer Nenner, der auf die Kritiker der Internationalisierung disziplinierend wirkte. Um die Intervention zu verteidigen, stellte die Clinton-Regierung Multilateralismus als nützliches Werkzeug dar. Diese Strategie half zwar bei der Vermittlung. Sie erforderte allerdings eine unverbindliche Rhetorik, die den Gegnern internationaler Sicherheitspolitik über die Debatte von 1995 hinaus Argumente lieferte.
Keywords: 300